Use of Automation Codecs Streaming Video Applications Based on Cloud Computing - Hero Wintolo; Anggraini Kusumaningrum; Handoko Widya Kusuma (Universitas Ahmad Dahlan, 2017)
Streaming technology is currently experiencing a great progress. Faster internet more users streaming. Streaming services that exist today there are still weaknesses in both the upload speed, streaming speed and limited types of video extensions that can be played. To resolve these problems then made a video streaming service based local area network with a system of cloud computing that can work effectively in terms of upload speeds, streaming and variations in video formats. Video streaming application is classified as a service IaaS (Infrastructure as a Service Cloud) in cloud computing. On the use of streaming applications the user does not need to convert the video, with the purpose of uploading process can be faster and applications can play a variety of video formats.